Raising awareness of carrier testing for hereditary haemoglobinopathies in high-risk ethnic groups in the Netherlands: a pilot study among the general public and primary care providers - Cornel Martina C; Rijmen Frank; de Lange-de Klerk Elly SM; Weinreich Stephanie S; de Kinderen Marja; Plass Anne (BMC, 2009)
Abstract Background In the Netherlands no formal recommendations exist concerning preconceptional or antenatal testing for carriership of hereditary haemoglobinopathies. Those at highest risk may be unaware of the possibility of carrier screening. While universal newborn screening has recently been introduced, neither preconceptional nor antenatal carrier testing is routinely offered by health care services to the general public. A municipal health service and a foundation for public information on medical genetics undertook a pilot project with the aim of increasing knowledge and encouraging informed choice. Two groups were targeted: members of the public from ethnic groups at increased risk, and primary health care providers. This study examines the effectiveness of culturally specific 'infotainment' to inform high-risk ethnic groups about their increased risk for haemoglobinopathies. In addition, the study explores attitudes and intentions of primary care providers towards haemoglobinopathy carrier testing of their patients from high-risk ethnic groups. Methods Informational sessions tailored to the public or professionals were organised in Amsterdam, and evaluated for their effect. Psychological parameters were measured using structured questionnaires based on the Theory of Planned Behaviour. Results The pre-test/post-test questionnaire showed that members of the public gained understanding of inheritance and carriership of haemoglobinopathies from the "infotainment" session (p < 0.01). Perceived behavioural control, i.e. the feeling that they could actually get tested if they wanted to, increased in the targeted age group of 18-45 years (N = 41; p < 0.05). 191 surveys were collected from general practitioners or midwives. Their attitude towards the education programme for high-risk ethnic groups was positive, yet they did not show strong intention to effectuate carrier testing of their patients on the basis of ethnicity. The main factor which explained their (lack of) intention was social norm, i.e. their perception of negative peer opinion (41% variance explained). The majority of primary health care providers felt that policy change was unnecessary. Conclusion The "infotainment" programme may have a positive effect on people from high-risk groups, but informed general practitioners and midwives were reluctant to facilitate their patients' getting tested. Additional initiatives are needed to motivate primary care providers to facilitate haemoglobinopathy carrier testing for their patients from high-risk backgrounds.